2008
DOI: 10.1111/j.1365-2443.2008.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of M2‐type pyruvate kinase activity by the cytoplasmic PML tumor suppressor protein

Abstract: The promyelocytic leukemia (PML) tumor suppressor protein accumulates in PML nuclear bodies (PML‐NBs), and can induce growth arrest, cellular senescence and apoptosis. PML has also been localized in the cytoplasm, although its function in this localization remains elusive. A general property of primary cancers is their high glycolytic rate which results from increased glucose consumption. However, the mechanism by which cancer cells up‐regulate glycolysis is not well understood. Here, we have shown that cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Various factors have been reported to control the switch between the dimeric and tetrameric forms of PKM2 (5,6,8,19,(36)(37)(38)(39)(40)(41)(42)(43)(44). For example, fructose-1,6-bisphosphate (fructose-1,6-P 2 ), a glycolytic intermediate, binds allosterically to PKM2 and facilitates the formation of the active tetramer.…”
Section: Glycolytic Functions Of Pkm2mentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors have been reported to control the switch between the dimeric and tetrameric forms of PKM2 (5,6,8,19,(36)(37)(38)(39)(40)(41)(42)(43)(44). For example, fructose-1,6-bisphosphate (fructose-1,6-P 2 ), a glycolytic intermediate, binds allosterically to PKM2 and facilitates the formation of the active tetramer.…”
Section: Glycolytic Functions Of Pkm2mentioning
confidence: 99%
“…A variety of molecules interact with PKM2 (5,6,8,14,18,19,21,23,24,28,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Many of them affect the glycolytic functions of PKM2, which directly regulate the Warburg effect.…”
Section: Nonglycolytic Functions Of Pkm2mentioning
confidence: 99%
“…PK activity was calculated at 25 1C by monitoring change of absorbance at 340 nm from 0 to 20 min. The activity of PK here was defined as the quantity of NADH oxidized by 1 mg of lysate protein or recombinant human PKM2 per minute (Ikeda and Noguchi, 1998;Shimada et al, 2008;Vander Heiden et al, 2010). Human recombinant PKM2 was either purchased from BPS Bioscience Inc, with an attached datasheet of characterization (Supplementary Figure 22), or from an in-house source as described in the preceding sections.…”
Section: Pk Activity Assaymentioning
confidence: 99%
“…The dimerization-tetramerization oscillation of PKM2 is a reversible process in normally dividing cells, which is regulated by the intracellular fructose 1,6-bisphosphate concentrations (20,21). Various studies based on post-translational modifications like tyrosine 105 phosphorylation (22), xenograft tumor model studies (23), and physical interaction of some proteins, such as Oct4 (24), PML (25), A-Raf (3), and pathogenic E7 (26,27) etc., have confirmed that reduced PKM2 activity promotes tumor progression (28). PKM2 dimer has also been demon-strated to act as a protein kinase and regulate gene transcription to affect important cellular functions (29).…”
mentioning
confidence: 99%